Brief Diagnostic Criteria for Temporomandibular Disorders (Tmd): Enhancing Sensitivity in Diagnosing Headache Attributed to Tmd (A Multi‐Centre Study) - Nykänen, Laura; Kämppi, Antti; Durham, Justin; Eli, Ilana; Freidman‐Rubin, Pessia; Keren, Lihi; Näpänkangas, Ritva; Shalev Antshel, Tamar; Tanner, Johanna; Teerijoki‐Oksa, Tuija; Winocur, Ephraim; Sipilä, Kirsi; et al. (Wiley, 2026)
Background
The brief Diagnostic Criteria for Temporomandibular Disorders (bDC/TMD) was developed to simplify the original DC/TMD for wider clinical use. While its diagnostic accuracy for most painful TMDs is acceptable, the sensitivity for headache attributed to TMD (HaTMD) was reported to be poor.
Objectives
To improve the diagnostic sensitivity of HaTMD within the bDC/TMD framework by reintroducing selected examination items from the original DC/TMD protocol.
Methods
This retrospective multicentre study used data from Finland and Israel. The cohort included 114 individuals previously diagnosed with HaTMD according to the DC/TMD and with myalgia and/or arthralgia diagnoses in both DC/TMD and bDC/TMD. Four examination items excluded from the bDC/TMD—E1b (headache location in temple), E4c (familiar headache on assisted opening), E5a/b (lateral movements) and E5c (protrusive movements)—were reintroduced individually. Four calibrated examiners reassessed each modified dataset. Inter-examiner reliability (Cohen's kappa) and diagnostic sensitivity were calculated using DC/TMD as the gold standard.
Results
Inter-examiner reliability for HaTMD diagnosis was almost perfect (κ = 0.81–1.00) across all items. Sensitivity improved markedly from the previously reported 0.16–0.38 to 0.82 (E1b)–0.90 (E5c). Item E1b (temple headache confirmation) was present in 95% of Finnish and 86% of Israeli cases, identifying it as the most representative finding.
Conclusion
Reintroducing item E1b into the bDC/TMD examination substantially increases the diagnostic sensitivity for HaTMD while maintaining brevity. Refinement of the painful TMD diagnostic decision tree and prospective validation of the modified bDC/TMD are recommended to ensure reliability and clinical applicability.